Adenovirus-associated paraphimosis. (July 2019) - Pollack, Alisa; Varma, Rick
We present the first reported case of paraphimosis associated with concurrent adenoviral urethritis and conjunctivitis in a heterosexual man. This case reinforces the need to consider adenovirus in the differential diagnosis of non-gonococcal urethritis and describes a potentially serious complication.